2006
DOI: 10.1111/j.1365-2265.2006.02696.x
|View full text |Cite
|
Sign up to set email alerts
|

A diurnal variation in testicular hormone production is maintained following gonadotrophin suppression in normal men

Abstract: The diurnal variation of testosterone in normal men is due to a change in secretion rather than in clearance and is largely LH driven. An endogenous rhythm in both testicular steroidogenesis (epitestosterone) and Sertoli cell function (inhibin B) is also present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
4
14
0
Order By: Relevance
“…It is known that the diurnal variation of E is comparable to the serum T level . As expected we noted a correlation between serum T and urinary E levels, both at baseline and after the administration of T. Luigi et al also found a correlation between serum total T and urinary E, and they suggested a possible peripheral conversion of exogenous T into E .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is known that the diurnal variation of E is comparable to the serum T level . As expected we noted a correlation between serum T and urinary E levels, both at baseline and after the administration of T. Luigi et al also found a correlation between serum total T and urinary E, and they suggested a possible peripheral conversion of exogenous T into E .…”
Section: Discussionsupporting
confidence: 89%
“…It is known that the diurnal variation of E is comparable to the serum T level. [26] As expected we noted a correlation between serum T and urinary E levels, both at baseline and after the administration of T. Luigi et al also found a correlation between serum total T and urinary E, and they suggested a possible peripheral conversion of exogenous T into E. [27] However, the main part of E synthesis is believed to be via a direct pathway from pregnenolone to 5α-androstane-3β,17α-diol catalyzed by CYP17. [18,28] In accordance with previous studies, we show that exogenous T administration represses the excretion rate of E. It has been assumed that this is due to an inhibition of LH secretion, but a correlation between LH and urinary E levels has only been verified in hypergonadotropic hypogonadal men (n=5).…”
Section: Discussionsupporting
confidence: 77%
“…15 Other factors, such as nutrient-sensitive hormones (such as insulin and adipokines) vary their circulating levels in part in response to the environment/behaviors, such as light/dark and feeding/fasting cycles, that typically occur in time-of-day-dependent patterns. 6, 7 Figure 1 and Table 1 summarize what is known regarding time-of-day-dependent oscillations in these and other endocrine factors, while below we provide additional detail for several of these factors.…”
Section: Circadian Rhythms In Stimulus-response Couplingmentioning
confidence: 99%
“…Additionally, there are circadian and seasonal rhythms to T concentrations [44-47]} and several types of social experiences can modulate plasma T profiles in both sexes, including sexual arousal, winning/losing sports competitions, exposure to an infant’s cries and providing nurturing care [48-57]. T concentrations can be modulated by social experiences as well as by exogenous drugs in both males [58,59] and females [60].…”
Section: Introductionmentioning
confidence: 99%